2014
DOI: 10.1128/aac.02111-13
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of a Bacitracin Resistance Network in Enterococcus faecalis

Abstract: Resistance of Enterococcus faecalis against antimicrobial peptides, both of host origin and produced by other bacteria of the gut microflora, is likely to be an important factor in the bacterium's success as an intestinal commensal. The aim of this study was to identify proteins with a role in resistance against the model antimicrobial peptide bacitracin. Proteome analysis of bacitracintreated and untreated cells showed that bacitracin stress induced the expression of cell wall-biosynthetic proteins and caused… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
81
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(98 citation statements)
references
References 36 publications
13
81
4
Order By: Relevance
“…Experimental evidence from a number of homologous systems, from B. subtilis, Staphylococcus aureus, Streptococcus mutans, Enterococcus faecalis, and Lactobacillus casei, confirms that this signaling pathway is a general characteristic of the Bce-type modules, and on a number of occasions, this pathway has been associated with lantibiotic resistance (107)(108)(109)(110)(111)(112)(113). For example, in L. lactis, a homologue named LlrG/KinG is found encoded to either side of the gene for a VanZ-like protein.…”
Section: Bcers-like Two-component Systemsmentioning
confidence: 88%
“…Experimental evidence from a number of homologous systems, from B. subtilis, Staphylococcus aureus, Streptococcus mutans, Enterococcus faecalis, and Lactobacillus casei, confirms that this signaling pathway is a general characteristic of the Bce-type modules, and on a number of occasions, this pathway has been associated with lantibiotic resistance (107)(108)(109)(110)(111)(112)(113). For example, in L. lactis, a homologue named LlrG/KinG is found encoded to either side of the gene for a VanZ-like protein.…”
Section: Bcers-like Two-component Systemsmentioning
confidence: 88%
“…lactis (383), but they have been characterized only for E. faecalis (384), Lb. casei (385), S. mutans (386), and S. thermophilus (387).…”
Section: Protecting the Cell Envelopementioning
confidence: 99%
“…In this organism, TCSs and ABC transporters are not genetically associated. One of the ABC transporters is essential for sensing bacitracin and eliciting a response (384). In response to bacitracin, the BceABRS system of S. mutans (also named MbrABRS) induces its own expression and that of three additional uncharacterized genes (386).…”
Section: Protecting the Cell Envelopementioning
confidence: 99%
“…In order to study the contribution of the BceRS system towards resistance against SDP, we first performed growth measurements of WT and a mutant carrying unmarked deletions of all three Bce-like systems (DbceRSAB DpsdRSAB DyxdJKLM-yxeA) of B. subtilis W168 (Gebhard et al, 2014) (TMB1518, referred to as the 'D3|bce' mutant hereafter) shown in Fig. 5(a).…”
Section: Bcers System Does Not Mediate Resistance Against Cannibalismmentioning
confidence: 99%